Tonicum Activity Test of Bidara Leaf Extract on Swimming Resistance of White Male Mice - Etika Yulianti; Nita Fajaryanti; Itsna Diah Kusumaningrum (Proceedings of the International Conference on Nursing and Health Sciences, 2020)
The bidara plant (Ziziphus mauritiana L.) is one of the medicinal plants used and trusted by the wider community for treatment. Traditionally this plant was used as a tonic. Objective : The purpose of this study was to prove the tonic activity of bidara leaf extract against white male mice (Mus musculus) and to determine the effective concentration of bidara leaf extract which has tonic activity against swimming resistance white male mice (Mus musculus). Method :This research was conducted in February - August 2019 at the Pharmacy Laboratory of the Kendal College of Health Sciences. The tools and materials used are mice, bidara leaves, ethanol, glassware, sonde and glass ponds.Leaf extraction of bidara was carried out by maceration method using 70% ethanol solvent. The design of this study was an experimental study (pre-experimental desings) in the form of statistical group comparisons. The tonic effect test was carried out using the mice swimming endurance method. Twenty five white malemice were divided into five groups. Group I mice were given 0.5% CMC Na (negative control), group II were given Fatigon (positive control) and groups III, IV, V were given bidara leaf extract concentrations of 50, 100 and 200 mg / kgBW orally. Data analysis was performed by comparing swimming times using the Kruskal-Wallis test and the Mann-Whitney test with a confidence level of 95%. Result : The results showed that there were group differences between treatments.Conclusions : The leaf extract of bidara (Ziziphus mauritiana L.) had tonic activity against white male mice (Mus musculus) with an effective concentration of 100 mg / kgBW.